2007
DOI: 10.1253/circj.71.565
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Estrogen Supplementation Following Ovariectomy Improves the Emotional Stress-Induced Cardiovascular Responses by Indirect Action on the Nervous System and by Direct Action on the Heart

Abstract: he incidence of cardiovascular diseases is low in pre-menopausal women, whereas it is increased in post-menopausal women. Estrogen supplementation therapy prevented the increase of cardiovascular diseases in post-menopausal women, 1 while recent metaanalysis of randomized trials showed no significant merits. 2 Effects of estrogen on cardiovascular diseases were attributed principally to the modification of serum lipid concentration and coagulation pathways, while direct actions of estrogen on the cardiovascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
92
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 156 publications
(99 citation statements)
references
References 43 publications
6
92
0
1
Order By: Relevance
“…19 Accumulating experimental and clinical evidence indicates that estrogens are actively involved in protecting the cardiovascular system against ischemic injury and RA. 6,8,20, 21 Although the biological effects of estrogen are less well defined in males than in females, a growing body of clinical evidence demonstrates that endogenous estrogen may protect cardiovascular health not only in female but also in male patients. 7,8 Therefore, understanding the pathophysiological mechanism of RA and how sex hormones protect the heart against RA is important not only for the prevention and control of RA but also for estrogen replacement therapy.…”
Section: Discussionmentioning
confidence: 99%
“…19 Accumulating experimental and clinical evidence indicates that estrogens are actively involved in protecting the cardiovascular system against ischemic injury and RA. 6,8,20, 21 Although the biological effects of estrogen are less well defined in males than in females, a growing body of clinical evidence demonstrates that endogenous estrogen may protect cardiovascular health not only in female but also in male patients. 7,8 Therefore, understanding the pathophysiological mechanism of RA and how sex hormones protect the heart against RA is important not only for the prevention and control of RA but also for estrogen replacement therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen hormones appear to be clearly protective in animal models, while the cardiodepressive effects of cathecolamine-excess are exacerbated in ovariectomized animals. 33 Myocytes express alpha and beta estrogen receptors. Estrogens increase production of cardioprotective factors such as AN, heat shock proteins, and protect the heart from toxic effects of catecholamine, calcium overload and oxidative stress.…”
Section: Tako-tsubo Cardiomyopathymentioning
confidence: 99%
“…This strong female predominance has been strongly associated with estrogen deficiency. Indeed, ovariectomised rats without estradiol supplementation exposed to immobilization stress had reduced left ventricular systolic function and increased heart rate and blood pressure in comparison with rats that were supplemented with estradiol (Ueyama et al, 2007). They also demonstrated that chronic supplementation with estrogen attenuated stress-induced sympatho-adrenal outflow from the brain to the heart (indirect action on the nervous system) and upregulated cardioprotective substances such as atrial natriuretic peptide and heat shock protein 70 in the heart (direct action on the heart).…”
Section: Estrogen Deficiencymentioning
confidence: 99%